Methods of Research of Foil Bearings in START-STOP Cycle in the Presence of Working Medium (Agricultural Engineering, 2019)
A method for testing sliding bearings with an elastic bearing liner was presented in the paper with a focus on the issue of selection of particular time intervals of the START-STOP test cycle. Then, results of the tests carried out according to the selected material combinations were presented. The working cycle of foil bearings tested on the test stand was performed in an automatic mode at the set number of sequences start-work-rundown-stop. Due to the highest use of sliding bearings during start and rundown of a machine, this type of tests is essential for selection of relevant sets of material for bearing elements. The article also presents the use of a thermo-visual camera for identification of additional thermal loads and manners of temperature stabilization in the test chamber.